Sufficient conditions for state observability in multi-substrate bioprocesses with additive growth dynamics - Nuñez, Sebastián (2014)
The distinguishability of the non-measured states is relevant for the design and implementation of state observers. The aim of this study is to examine the observability of a fed-batch multi-substrate process with additive growth rate. Based on the model equations, sufficient conditions to fulfill the observability rank condition were determined. Results for threesets of outputs were analyzed for Monod and Haldane models.